Perianal leiomyosarcoma as a rare sequela of rectal cancer radiotherapy: a case report - Chen, Chaopeng; Cai, Wenping; Li, Yujiao; Ren, Junqi; Xu, Zhibin; Pang, Lijuan; Dai, Weiping (Frontiers in Oncology, 2024)
Radiation-induced sarcomas (RIS) are iatrogenic malignancies that arise following high-dose radiotherapy, posing a significant clinical challenge due to their poor prognosis and resistance to conventional treatments. The incidence of RIS is increasing with advancements in radiotherapy techniques. This report presents a case of a 71-year-old male diagnosed with stage III rectal adenocarcinoma treated with neoadjuvant chemoradiotherapy and curative surgery. Three years postoperatively, he developed a low-grade radiation-induced leiomyosarcoma in the perianal region. Histopathological examination confirmed a spindle cell neoplasm with notable immunohistochemical markers. RIS often presents as aggressive high-grade tumors resistant to radiotherapy and chemotherapy, necessitating surgical resection as the primary treatment. This case underscores the importance of long-term surveillance post-radiotherapy and highlights the need for innovative therapeutic strategies, including immunotherapy. Despite being rare, RIS poses a significant risk following cancer treatment, making early detection through vigilant monitoring and advancements in therapeutic approaches crucial for improving patient outcomes.